Fungal colonization and biomineralization for bioprotection of concrete. (1st January 2022) - Zhao, Jiayue; Dyer, Thomas; Csetenyi, Laszlo; Jones, Rod; Gadd, Geoffrey Michael
Abstract: Concrete can face serious deterioration issues due to different physical, chemical, or biochemical factors. Structural integrity and durability are significantly impaired by cracks which provide channels for water or gases to penetrate concrete matrices, ultimately attacking the steel reinforcements. In this research, we show that a urease-positive fungus, Neurospora crassa, can deposit calcium carbonate on mortar through microbiologically-induced calcium carbonate precipitation (MICP) forming a dense biomineralized mycelial network resulting in a protective coating on Portland cement, fly ash, and ground granulated blast furnace slag based mortar. Rietveld refinement of X-ray diffraction data showed that greater amounts of calcium carbonate were precipitated with increasing mortar porosity. Water repellence was enhanced after fungal colonization and carbonate biodeposition on the surface, and water absorption coefficients improved 17% at least after development of the boioprotective coating. Overall, this work demonstrates that fungal biomineralization could act as biocement to protect porous mineral-based materials from water infiltration, thus improving their durability. Graphical abstract: Image 1 Highlights: A urease positive fungus was able to colonize and protect porous infrastructure materials. Calcite accumulated on the surface of concrete resulting from fungal-induced calcium carbonate precipitation during growth. Physical shielding by biomass and pore clogging by calcium carbonate were predominant mechanisms involved in bioprotection. The formation of a biocrust can prevent water infiltration into the underlying concrete.